การพัฒนารูปแบบการเรียนการสอนที่เน้นทักษะกระบวนการเพื่อส่งเสริมความสามารถด้านการคิดวิเคราะห์ สำหรับนักศึกษาพยาบาล วิทยาลัยพยาบาลบรมราชชนนี ชลบุรี - เหลืองรัตนมาศ, ลัดดา; ศุกระแพทย์, วรพนิต (วารสารวิจัยทางวิทยาศาสตร์สุขภาพ วิทยาลัยพยาบาลบรมราชชนนี จังหวัดนนทบุรี, 2016)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัจจุบันและความต้องการด้านการจัดการเรียนรู้เพื่อพัฒนาการคิดวิเคราะห์ของนักศึกษา 2) พัฒนารูปแบบการเรียนการสอนที่เน้นทักษะกระบวนการ 3) ศึกษาประสิทธิผลของรูปแบบการเรียนการสอน โดยมีรูปแบบการวิจัยเป็นวิจัยและพัฒนา กลุ่มตัวอย่างเป็นนักศึกษาพยาบาลชั้นปีที่ 2 วิทยาลัยพยาบาลบรมราชชนนี ชลบุรี จำนวน 118 คน ที่เรียนวิชาพยาธิสรีรวิทยา เครื่องมือวิจัยประกอบด้วย แผนการสอนที่ใช้รูปแบบการเรียนการสอนที่เน้นทักษะกระบวนการ และแบบทดสอบวัดการคิดวิเคราะห์ ซึ่งมีค่าความเชื่อมั่นเท่ากับ 0.82 ค่าความยากง่ายอยู่ระหว่าง 0.23-0.73 แบบสอบถามความสามารถของตนเองด้านการคิดวิเคราะห์และความพึงพอใจที่มีต่อรูปแบบ วิเคราะห์ข้อมูลโดยใช้ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และสถิติที (t-test) วิเคราะห์ข้อมูลเชิงคุณภาพโดยวิเคราะห์เชิงเนื้อหา (Content analysis) ผลการวิจัยพบว่า การจัดการเรียนการสอนในปัจจุบัน อาจารย์ใช้วิธีการสอนที่หลากหลายแต่วิธีที่ใช้มากที่สุดคือ การบรรยาย รวมทั้งรูปแบบการเรียนการสอนเน้นทักษะกระบวนการกลุ่มประกอบด้วย 7 ขั้นตอน ได้แก่ รู้ฉันรู้เธอ ปลุกความคิด พินิจไตร่ตรอง มองหาความเชื่อมโยง สร้างข้อคำถาม ระดมสมอง สรุปรวบยอดและถ่ายทอดความคิด และผลการศึกษาประสิทธิผลของรูปแบบ พบว่า นักศึกษามีคะแนนสอบด้านการคิดวิเคราะห์หลังเรียนผ่านเกณฑ์ร้อยละ 70 ร้อยละ 88.98 นักศึกษาประเมินความสามารถของตนเองด้านการคิดวิเคราะห์หลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 และนักศึกษามีความพึงพอใจต่อการเรียนโดยใช้รูปแบบในภาพรวมอยู่ในระดับมาก ด้านผู้สอนมีค่าเฉลี่ยสูงที่สุด สรุปได้ว่ารูปแบบนี้ส่งเสริมการคิดวิเคราะห์ของนักศึกษา The purpose of this research were: 1) to study the current situation and needs in learning management system for analytical thinking of students; 2) to develop instruction model emphasizing process skill; and 3) to study the effectiveness of the model. The research design of this study was Research and Development. The model was undertaken with 2nd year nursing students, Boromarajonani College of Nursing Chon Buri. The sample comprised 118 students who studied in pathophysiology subject. The research instruments consisted of: 1) lesson plan; 2) The analytical thinking test with reliability at 0.82 and difficulty level was between 0.23-0.73; and 3) the opinion questionnaires toward self analytical thinking ability and the model satisfaction with reliability at 0.95. The data were analyzed by using mean, standard deviation and t-test. Qualitative data were analyzed by using content analysis. Results of the study were as follows: 1) the current situation, various teaching methods were used but the main method was lecture; 2) the instructional model emphasizing process skill to enhance analytical thinking consisted of 7 steps; invigorate, stimulate thinking process, classify and related element, develop question, group discussion, summarize the content and transmission; and 3) The effects of model evaluation was that 105 students or 88.98 % had score in analytical thinking higher than criterion of 70%. In addition, the analytical thinking ability of the students after participating in learning process was higher than before learning with the significance level of 0.01. Moreover, the student were satisfied with the whole instructional at high level, especially the part of teacher (X = 4.07, SD = 0.41). In conclusion, this model could developed student’s analytical thinking skill.